Resective and Regenerative Surgical Treatment of a Dentigerous Cyst Associated with an Impacted Lower Canine with Transmigration: a Case Report - Ganzaroli, Vinícius Franzão; Meira, Juliana de Aguiar Silveira; Bacelar, Ana Carolina Zucon; Paludetto, Laura Vidoto; Pereira, Rodrigo Isaias Lopes; Lopes Pereira, Estêvão; Salzedas, Leda Maria Pescinini; Ponzoni, Daniela (ARCHIVES OF HEALTH INVESTIGATION, 2025)
To report the surgical management of a dentigerous cyst associated with a transmigrated mandibular canine using resective and regenerative techniques. A 28-year-old male presented with mandibular swelling, numbness, and pain. Imaging revealed a bone lesion associated with an impacted, transmigrated canine. Treatment included cyst decompression, enucleation, and guided bone regeneration (GBR) using biomaterials and a collagen membrane. Follow-up evaluations were conducted at 3, 6, and 12 months. Histopathology confirmed a dentigerous cyst. Post-operative healing was successful, with no recurrence, pain, or paresthesia. Radiographic evaluations showed significant bone repair and no signs of lesion recurrence. The combination of decompression, enucleation, and GBR effectively treated this rare case, minimizing bone defects and ensuring favorable outcomes. This approach is recommended for similar cases.